2018
DOI: 10.1242/dev.160721
|View full text |Cite
|
Sign up to set email alerts
|

L(3)mbt and the LINT complex safeguard cellular identity in the Drosophila ovary

Abstract: Maintenance of cellular identity is essential for tissue development and homeostasis. At the molecular level, cell identity is determined by the coordinated activation and repression of defined sets of genes. The tumor suppressor L(3)mbt has been shown to secure cellular identity in Drosophila larval brains by repressing germline-specific genes. Here, we interrogate the temporal and spatial requirements for L(3)mbt in the Drosophila ovary, and show that it safeguards the integrity of both somatic and germline … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 62 publications
6
25
0
Order By: Relevance
“…To test whether nos in FCs is responsible for the egg chamber fusion in lky KO ovaries, we analyzed ovaries from flies homozygous for both lky KO and hypomorphic alleles of nos ( nos L7 /nos BN ). Strikingly, we observed a significant decrease in the frequency of egg chamber fusion in these flies (Figure 5C), and overexpression of nos in FCs using the c587Gal4 driver caused egg chamber fusion (Figure 5D), consistent with the previous report [60]. Together, these data suggest that nos gene product leaks from the germline into somatic FCs in lky KO ovaries, resulting in egg chamber fusion.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…To test whether nos in FCs is responsible for the egg chamber fusion in lky KO ovaries, we analyzed ovaries from flies homozygous for both lky KO and hypomorphic alleles of nos ( nos L7 /nos BN ). Strikingly, we observed a significant decrease in the frequency of egg chamber fusion in these flies (Figure 5C), and overexpression of nos in FCs using the c587Gal4 driver caused egg chamber fusion (Figure 5D), consistent with the previous report [60]. Together, these data suggest that nos gene product leaks from the germline into somatic FCs in lky KO ovaries, resulting in egg chamber fusion.…”
Section: Resultssupporting
confidence: 90%
“…A previous study has demonstrated that misexpression of the germline component nanos (nos) in FCs is sufficient to cause the phenotype of egg chamber fusion [60]. In their study, nos overexpression in FCs was sufficient to cause egg chamber fusion, and introducing a hypomorphic allele of nos ( nos L7 /nos BN ).…”
Section: Resultsmentioning
confidence: 99%
“…L(3)mbt’s function as a repressor of unscheduled gene programs is not limited to the somatic cells of the larval brains. Loss of l(3)mbt in some Drosophila cell lines and in the somatic cells of the ovary leads to the ectopic activation of germline genes, including components of the PIWI ping-pong cycle, vas , nos , and others ( 26 , 27 ). Loss of l(3)mbt in the female germline results in the ectopic activation of testis and neuronal genes ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study in Drosophila showed a role for the conserved factor L(3)mbt in lineage-inappropriate gene repression in the female germline and soma (Coux et al, 2018). The mammalian L3MBTL2 homolog (involved in PRC1.6) is also required for the repression of germline-specific genes in mouse ESCs (Maeda et al, 2013;Stielow et al, 2018;Tatsumi et al, 2018).…”
Section: H3k9me3 and Gene Silencing In Germ Cellsmentioning
confidence: 99%